Estimativas de acessibilidade a empregos e serviços públicos via transporte ativo, público e privado nas vinte maiores cidades do Brasil no período 2017-2019 - Rafael Henrique Moraes Pereira; Carlos Kauê Vieira Braga; Daniel Herszenhut; Marcus Saraiva; Diego Bogado Tomasiello (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– One of the main goals of transportation policies is to improve the people's access to employment opportunities, public services, and amenities. For this reason, an increasing number of transportation and funding agencies have sought to incorporate accessibility studies in the planning and assessment of their transportation policies and infrastructure investments. However, there is still very limited data on urban accessibility in Brazil due to computational and methodological challenges. This study presents a comprehensive database with urban accessibility estimates created by the Access to Opportunities Project (Projeto Acesso a Oportunidades), and introduce the methods used in its development. The database consists of a spatial grid of hexagons of high spatial resolution that aggregates estimates of accessibility to jobs (low-, medium- and high-qualification) and public services, such as schools (early childhood, primary and high school), health facilities (hospital and ambulatory services of low, medium and high complexity) and reference centers for social assistance (Cras). These estimates are calculated using different accessibility indicators by transport mode (walking, cycling, public transport, and car), for different times of the day (peak and off-peak) and for different population groups according to income levels, race, gender, and age. In this edition, the database brings information for the period from 2017 to 2019 based on a single consistent methodology for the twenty largest cities in Brazil. This database is made publicly available by the Ipea through the website of the Access to Opportunities Project and through the R package aopdata. We hope this work will allow researchers and policy makers to use urban accessibility estimates to inform research as well as the planning and evaluation of public policies.
10419/284858
Keywords: 330; urban accessibility; urban transport; public transport; walking; bicycle; automobile; jobs; health; education; social assistance; public services; cities; Brazil